The Effectiveness Of Urine as A Subtitute Nitrogen Fertilizer on Nursery Cocoa Plants (Theobrema cacao, L) - Arnadi Gunawan; Elza Zuhry; Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research explains comparison of effectiveness human urine with urea fertilizer on the growth of cocoa seedlings (Theobroma cacao, L). This Research use Completely Randomized Design (CRD) with seven treatments, namely: (1) U0 = 2 g Urea, (2) U1 = 50 ml human urine without fermentation, (3) U2 = 100 ml human urine without fermentation, (4 ) U3 = 50 ml fermentation of human urine for 7 days, (5) U4 = 100 ml fermentation of human urine for 7 days, (6) U5 = 50 ml fermentation of human urine for 14 days, and (7) U6 = 100 ml fermentation of human urine for 14 days. Each treatment was repeated 3 times, thus obtained 21 experimental units. in this research, parameters measured were seedling height, number of leaves, leaf area, stem diameter, root volume, wet weight, dry weight of plants, the ratio of roots crown, and seed quality index of cocoa seedlings. The data obtained in this study continued using Duncan's Multiple Range Test 5%. This study shows that the use of human urine is more effective than the use of urea fertilizer, especially on the use of 100 ml of human urine without fermentation. The use of human urine 100 ml without fermentation, can significantly improve seedling height, leaf number, root volume, wet weight, and quality of cocoa seedlings index. Keywords: cocoa seedlings, human urine, urea fertilizer.